P–749 Knowledge of women undergoing surgery for endometrioma regarding the impact of the disease and its treatment on ovarian reserve and fertility. (6th August 2021) - Horan, M; Glover, L; Downey, P; Wingfield, M
Abstract: Study question: Do women undergoing surgery for endometrioma due to pain, a cyst and/or subfertility understand the impact of the disease and its treatment on ovarian reserve and fertility. Summary answer: The majority of women treated in a fertility setting are well informed compared to those in a general medical setting. What is known already: Infertility affects 30% to 50% of women with endometriosis. Ovarian endometriomas are reported in 17–44% of infertile women with endometriosis and are typically associated with more severe disease. Endometriomas are associated with diminished ovarian reserve, due to the endometrioma per se or due to surgical interventions required to treat and excise the disease. ESHRE guidelines recommend that women should be informed pre-operatively of the potential reduction in ovarian reserve associated with surgery and that ovarian reserve tests should be performed when future fertility is a concern. Study design, size, duration: In conjunction with our histopathology colleagues we identified a cohort of women with a histological diagnosis of one or more ovarian endometriomas who underwent surgery in our unit between 2010 and 2019. We developed a scoping questionnaire, targeted at women currently over the age of 40, who had previously undergone surgery for endometrioma under the age of 35. Patients were contacted by telephone and consent obtained to send an email with a survey link. Participants/materials, setting, methods: We identified 47 women who had a histological diagnosis of endometrioma. Of these, 30 were contactable by telephone, of whom 29 consented to being sent information regarding the study and a link to the questionnaire. 21 women completed the survey. Respondents were divided into 2 groups for analysis. Group 1 cited 'fertility' or 'both pain and fertility' as an indication for their surgery while group 2 had 'pain' or 'ovarian cysts' but no fertility concerns. Main results and the role of chance: The majority (62%) of patients were diagnosed with endometriosis while aged 25–34. The indication for surgery was evenly divided between pain (32%), fertility (37%) and ovarian cysts (37%). 60% of women reported having endometriomas diagnosed preoperatively. Striking differences were noted between groups 1 and 2. Of the women who cited 'fertility' or 'both pain and fertility' (n = 9) as an indication for their surgery, 78% (n = 7) reported being aware of any possible negative impact of endometriosis on their fertility, with 78% also being aware of the possible negative impact of surgery for endometriosis on their fertility. This compared to only 36% (n = 4) and 27% (n = 3) respectively in Group 2. In group 1, 56% (n = 5) remembered having an AMH level checked pre operatively while 78% (n = 7) also had an ultrasound pre-operatively. In contrast, only 33% (n = 3) of Group 2 remember having an AMH level checked pre operatively though 64% (n = 7) had an ultrasound pre-operatively. Of those whose surgery was performed by a fertility specialist, 75% (n = 6) reported being aware of the impact of endometriosis and also the impact of surgery on ovarian reserve, compared to 44% (n = 4) of those who surgery was performed by a non-fertility specialist. Limitations, reasons for caution: This is a retrospective study and the numbers are small. We were only able to identify women with an endometrioma via pathology records, so those with no excision of disease (eg those who had ablation of an endometrioma) were excluded from this analysis. Wider implications of the findings: This suggests the majority of patients treated in a fertility setting are counselled regarding the benefit of surgery but also the risk to ovarian reserve. This is not the case in other settings. It is time to disseminate guidelines such as those produced by ESHRE to our general gynaecology colleagues. Trial registration number: Not applicable